ECOLOGICAL LUBRICANTS UTILIZATION - Stefan GHIMISI (Fiabilitate şi Durabilitate)
The paper addresses the use of environmentally friendly lubricants in industry They are efficient lubricants with very good tribological properties. However, their thermal and hydrolytic stability are limited and need to be improved. Thus, at present, the use of pure (unmodified) vegetable oils is limited only in applications with total lubricant loss, such as chain saw lubricants, mold oils and hydraulic fluids with a very low thermal stress.